2002
DOI: 10.1038/sj.bjc.6600009
|View full text |Cite
|
Sign up to set email alerts
|

Weight at birth and adolescence and premenopausal breast cancer risk in a low-risk population

Abstract: We assessed breast cancer risk in relation to weight at birth and adolescence. In-person interviews were completed with the biological mothers of women aged 45 years and younger who participated in the Shanghai Breast Cancer Study in 1996 -98 (288 cases, 350 controls). After adjustment for confounding, women who were 4000 g or more at birth were not at increased risk of breast cancer (odds ratio=0.7; 95% confidence interval 0.4 -1.4) relative to women whose birth weight was 2500 -2999 g. Compared with women of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
3
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 32 publications
4
64
3
2
Order By: Relevance
“…Most studies find evidence of a positive association between birth weight and breast cancer risk, but several have not (Ekbom et al, 1997;Sanderson et al, 1998Sanderson et al, , 2002Titus-Ernstoff et al, 2002;Hodgson et al, 2004). Although not associated overall in our data, risk was elevated, albeit not statistically significantly, with high birth weight in younger women consistent with previous observations (Michels et al, 1996;Sanderson et al, 1996;De Stavola et al, 2000;Innes et al, 2000;Mellemkjaer et al, 2003;McCormack et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Most studies find evidence of a positive association between birth weight and breast cancer risk, but several have not (Ekbom et al, 1997;Sanderson et al, 1998Sanderson et al, , 2002Titus-Ernstoff et al, 2002;Hodgson et al, 2004). Although not associated overall in our data, risk was elevated, albeit not statistically significantly, with high birth weight in younger women consistent with previous observations (Michels et al, 1996;Sanderson et al, 1996;De Stavola et al, 2000;Innes et al, 2000;Mellemkjaer et al, 2003;McCormack et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…While earlier studies controlled for social class (Ekbom et al, 1997;De Stavola et al, 2000;Sanderson et al, 2002;Vatten et al, 2002Vatten et al, , 2005Titus-Ernstoff et al, 2002;McCormack et al, 2003McCormack et al, , 2005Lahmann et al, 2004;Lahmann et al, 2004;dos Santos Silva et al, 2004), none found evidence of confounding of the birth weight and breast cancer association. Only one investigated the interaction of birth weight and education (Titus-Ernstoff et al, 2002), reporting a stronger association of high birth weight with breast cancer risk in women whose fathers were the most educated.…”
Section: Discussionmentioning
confidence: 91%
“…Similar to several previous reports, we found a linear association between breast cancer and birth weight. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] We also found an inverse association between birth weight and testicular cancer, which thereby strengthens the previous findings. [40][41][42][43][44][45][46] To our knowledge, only 2 smaller studies published to date have previously addressed the association between the overall risk of cancer and birth weight.…”
Section: Discussionsupporting
confidence: 80%
“…With great interest, I read the different results found for birth weight and birth length on adult breast cancer risk reported by Vatten (2002) and Sanderson (2002). Both articles referred to a hypothesis on early through postconception life events and breast cancer risk (Trichopoulos, 1990).…”
Section: Sirmentioning
confidence: 99%